2019
DOI: 10.33155/j.ramd.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of three different warm-up protocols on maximal isokinetic strength in young men

Abstract: Objective: To investigate the acute effect of three different warm-up protocols on a maximal isokinetic strength test. Methods: Twenty-two male, recreational athletes involved in regular resistance training were evaluated. Subjects performed a maximal isokinetic strength test of the knee extensors in an isokinetic dynamometer after completing a control session or one of the following warm-up protocols using a randomized design: a general warm-up, stretching warm-up, or specific warm-up. The comparison be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our study did not observe improved lower limb performance after SW. As for the upper limbs, SW resulted in decreased repetition performance compared to SS and CC. This result is intriguing because SW are frequently related to improvements in acute performance in resistance exercises (1,16,21,23), although this is not universal (20,22). This nding may be associated with the upper limbs characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Our study did not observe improved lower limb performance after SW. As for the upper limbs, SW resulted in decreased repetition performance compared to SS and CC. This result is intriguing because SW are frequently related to improvements in acute performance in resistance exercises (1,16,21,23), although this is not universal (20,22). This nding may be associated with the upper limbs characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…In the study of Rodrigues and collaborators, [23] three different types of warmup were compared: a general warm-up, a specific warm-up, and a warm-up through stretching, to understand whether it would influence maximal isokinetic training. The results reported that the three types of warm-up had no adverse effect or any type of improvement in acute muscle strength.…”
Section: Discussionmentioning
confidence: 99%